(untitled) (Scientia Agricola, 2013)
Fusarium oxysporum f. sp. passiflorae W.L. Gordon (FOP) is one of the most important fungal pathogens of passion fruits. Understanding molecular variation of isolates from different areas is of utmost importance. Molecular fingerprinting on 14 isolates of FOP were conducted using AFLP molecular markers (Amplified Fragment Length Polymorphism), and their genetic variability were estimated. Twenty-five AFLP primer combinations were selected for amplification of FOP isolates and one for Fusarium oxysporum f. sp. cubense W.C. Snyder & H.N. Hansen (FOC), resulting in 99% polymorphic fragments, with an average of 40 fragments per primer combination. Specific fingerprints could be generated for most of the isolates evaluated; we observed a high power of discrimination of the AFLP primer combinations, with the presence/absence of up to 26 specific fragments per isolate. Thus, specific fingerprinting was obtained for 10 of the 15 isolates analyzed. The values of the polymorphic information content, the index and the resolving power of the markers showed wide variation and reflected the high informative contents of the primers used in the characterization of the FOP isolates. The FOP isolates were divided into four groups, irrespective of their geographic origins, with the allocation of 5, 7, 1 and 1 FOP isolates into Groups II, III, IV and V, respectively. A wide genetic diversity was observed in FOP isolates, which should be taken into consideration when implementing strategies for the improvement of passion fruit in the search for cultivars with multiple resistance to different isolates.